Three Polymorphs and Two Hydrates of a Multidrug Crystal Involving Gefitinib and Rhein: Characterization, Stability, and Solubility Aspects - Zhang, Fang; Long, Xiang-Tian; Ren, Bo-Ying; Dai, Xia-Lin; Lu, Tong-Bu; Chen, Jia-Mei (Crystal growth & design, 2024)
Multidrug crystals, comprising multiple drugs in the same crystal lattice, can be used to develop drug combinations with improved physicochemical properties. The investigation on polymorphism of a given multidrug crystal aids in finding the optimal solid form for the development of combined formulations. In this work, three polymorphs (GTB−RH I, GTB−RH II, and GTB−RH III) and two hydrates (GTB−RH·4.25H 2 O and GTB−RH·1.25H 2 O) of a multidrug crystal involving gefitinib (GTB) and rhein (RH) were successfully obtained and fully characterized by X-ray diffraction (XRD), 1H nuclear magnetic resonance (1H NMR), thermogravimetric analysis (TG), differential scanning calorimetry (DSC), Fourier transform infrared (FT-IR), and dynamic vapor sorption (DVS) measurements. Thermal analysis reveals that GTB−RH I and GTB−RH II are monotropically related, while GTB−RH II and GTB−RH III are enantiotropically related. GTB−RH I is a metastable form, GTB−RH II is the stable form at lower temperature, and GTB−RH III is the stable form at higher temperature. The transition of GTB−RH II to GTB−RH III occurs upon heating to 190 °C. Slurry conversion experiments indicate that GTB−RH·4.25H 2 O is the stable form in aqueous solutions, while GTB−RH II is the stable form in nonaqueous solutions. Accelerated stability tests show that GTB−RH·1.25H 2 O and GTB−RH I converted to GTB−RH·4.25H 2 O, while GTB−RH·4.25H 2 O, GTB−RH II, and GTB−RH III remained intact up to three months. In addition, dissolution experiments demonstrate the apparent solubility of GTB and RH in the following order: GTB−RH III > GTB−RH II > GTB−RH I > GTB−RH·1.25H 2 O > GTB−RH·4.25H 2 O. This work shows that GTB−RH III has great potential to be developed into a combined formulation as it exhibits simultaneously and significantly improved solubility for both GTB and RH.